1994
DOI: 10.1007/bf02484415
|View full text |Cite
|
Sign up to set email alerts
|

The role of radiation therapy in vertebral hemangiomas without neurological signs

Abstract: We describe 5 patients with vertebral haemangiomas treated by radiotherapy of 30-40 Gy, 2-3 Gy/day. The management of vertebral haemangiomas is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…Only one patient had a complete response (100%), good response (> 50%) was seen in two patients and partial response (< 50%) in three (2). However, this therapy carries the risk of radiation-induced secondary sarcomas or the development of radionecrosis (13). Embolization requires the use of a medullar angiography in order to ensure that the hemangioma is not vascularised by a spinal artery (14).…”
Section: Discussionmentioning
confidence: 99%
“…Only one patient had a complete response (100%), good response (> 50%) was seen in two patients and partial response (< 50%) in three (2). However, this therapy carries the risk of radiation-induced secondary sarcomas or the development of radionecrosis (13). Embolization requires the use of a medullar angiography in order to ensure that the hemangioma is not vascularised by a spinal artery (14).…”
Section: Discussionmentioning
confidence: 99%
“…We found 17 previous studies (3,7,20,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) on the use of radiotherapy in vertebral hemangioma for the years 1926 through 2004. An analysis of the 228 patients in this body of research treated solely with radiotherapy showed that complete pain relief was obtained in 54 percent of the patients, and partial response was obtained in 32 percent.…”
Section: Resultsmentioning
confidence: 84%
“…Radiation therapy is reported in patients with involvement of multiple vertebral levels [3,8]. The recommended dose is 2 Gy per day for several weeks up to a total of 30-40 Gy [11]. Patients with neurologic symptoms should undergo laminectomy before radiation therapy initiation, because the edema secondary to radiation therapy can worsen the symptoms [21].…”
Section: Discussionmentioning
confidence: 99%